The Use of Intraoral Scanner Imaging in the Diagnosis of Periodontitis - A retrospective pilot study - Hwang, Sean. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Periodontology.; Advisor: Robert Gyurko.; Committee: Wael Att, Yo-wei Chen, Lorenzo Mordini, and Sarah Pagni.; Keyword: Dentistry.